Contributions of Innovation and Entrepreneurship Education to Entrepreneurial Intention with Entrepreneurial Motivation as an Intervening Variable in Vocational High School Students - Muh. Yahya; Andika Isma; Andi Naila Quin Azisah Alisyahbana; Ilham Abu (Pinisi Journal of Entrepreneurship Review, 2023)
Unemployment is a major problem in Indonesia. This happens because Indonesia is a country with a high population growth rate, which affects the competition for jobs. One way that is considered quite effective to overcome the problem of unemployment is to create or increase the number of entrepreneurs. This study aims to determine the direct effect and indirect effect of Innovation, Entrepreneurship Education, Entrepreneurial Intention, on Entrepreneurial Motivation. The research method used in this research is quantitative. The independent variables are Innovation (X1) and Entrepreneurship Education (X2), the dependent variable is Entrepreneurial Intention (Y), and the Intervening variable is Entrepreneurial Motivation (Z). The number of respondents in this study were Vocational High School students with a sample of 32 students. Based on the results of research that has been done, directly and indirectly Innovation, entrepreneurship education, entrepreneurial intention, and motivation have a significant effect on entrepreneurial intention in Vocational Students.